1980
DOI: 10.1210/endo-106-2-547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosterone on Insulin and Glucagon Secretion by the Isolated Perfused Rat Pancreas*

Abstract: The in vitro effect of corticosterone in insulin and glucagon secretion has been examined in the isolated perfused rat pancreas preparation. COrticosterone at physiological concentrations was found to inhibit acutely and strongly the secretion of insulin induced by both glucose and arginine and to potentiate the output of glucagon in a glucose-free medium or when induced by arginine. Phentolamine, an alpha-adrenergic blocking agent, diminished the strong inhibitory effect of corticosterone on insulin secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 27 publications
6
48
0
Order By: Relevance
“…2A, left). This inhibitory action involves a-adrenergic signalling due to the blockage of GCs' effect by phentolamine (a non-selective a-adrenergic antagonist; Barseghian & Levine 1980). This rapid impact of GCs is not reproduced by synthetic steroids.…”
Section: Acute Effects Of Gcsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A, left). This inhibitory action involves a-adrenergic signalling due to the blockage of GCs' effect by phentolamine (a non-selective a-adrenergic antagonist; Barseghian & Levine 1980). This rapid impact of GCs is not reproduced by synthetic steroids.…”
Section: Acute Effects Of Gcsmentioning
confidence: 99%
“…One study reported that corticosterone (10 K7 M) potentiated glucagon release induced by a glucose-free medium or arginine in isolated perfused rat pancreas (Barseghian & Levine 1980). In contrast, incubation of mouse pancreatic islets with dexamethasone (0.5-50 nM), corticosterone (50 nM) or 11-dehydrocorticosterone (50 nM) for 2 h reduced glucagon secretion induced by low glucose levels, effects that were reversed by a GR antagonist (Swali et al 2008).…”
Section: Acute Effects Of Gcs On A-cell Function and Glucagon Releasementioning
confidence: 99%
“…No clinical signs of glucocorticoid excess have been reported in humans taking oestrogens, but glucocorticoids have a number of effects in animals that parallel those seen with oestrogens, including suppression of the early insulin response to glucose [34], pancreatic hypertrophy, an increased insulin response to glucose and prevention of diabetes [8]. Importantly, the enhanced insulin response to oestrogen is not seen in adrenalectomised animals, but is restored by glucocorticoid administration [35].…”
Section: Oestrogen-induced Changes In Progesterone Receptorsmentioning
confidence: 99%
“…Receptor binding for progesterone present in the pancreas [10] Exposure of perfused pancreas to progesterone does not affect insulin release [32] Oestrogens increase receptor binding for progesterone in the pancreas [10] In vivo effects of progesterone on insulin secretion could be secondary to weight gain and insulin resistance Exposure of isolated pancreatic islets to progesterone augments insulin release [33] Progesterone administration to animals augments isolated islet insulin release [11] Oestrogen-induced increases in glucocorticoid activity Glucocorticoid levels are increased in women taking oestrogens [4] Suppression of first-phase insulin secretion by oestrogens is still apparent following adrenalectomy [35] Effects of glucocorticoids in humans on first-phase insulin release resemble those of oestrogens [34] Trophic effect of oestrogens on the pancreas is still apparent following adrenalectomy [8] Glucocorticoids have a trophic effect on the pancreas and diminish incidence of diabetes in animal models [8] Augmentation of insulin secretion by oestrogen is not seen in adrenalectomised animals but is restored by corticosteroids [35] Oestrogen-induced increases in growth hormone activity Growth hormone levels are increased in women taking oestrogens [36] Changes in growth hormone do not relate to changes in glucose metabolism [36] Growth hormone stimulates insulin secretion and DNA synthesis in isolated islets [38] IGF levels are unaffected by oestrogens [37] Favourable effect of oestrogens on the pancreas is apparent following hypophysectomy [9] Oestrogen-induced decreases in glucagon sensitivity and secretion Glucagon-induced hyperglycaemia is diminished by oestrogens [40] Oral contraceptive oestrogens do not affect plasma glucagon concentrations in humans [50] Ovariectomy increases plasma glucagon concentrations and enhances the hyperglycaemic action of glucagon [41] Following ovariectomy, oestrogen administration decreases the hepatic portal vein insulin glucagon ratio [43] Following ovariectomy, oestrogen administration decreases the hyperglycaemic action of glucagon [41] Key references are given. Evidence is from animal studies, except where stated…”
Section: Oestrogen-induced Changes In Growth Hormonementioning
confidence: 99%
“…The effects of glucocorticoid on insulin secretion are dependent upon the dose and duration of administration [8]. While most studies report inhibition of insulin secretion by glucocorticoids [5,[9][10][11], long-term culture in hydrocortisone [12] and dexamethasone-treatment of islets from adrenalectomised rats [13] increase insulin release. However, transgenic mice overexpressing GR (also known as NR3C1) specifically in the beta cell have impaired glucose tolerance due to decreased insulin release, suggesting a direct inhibitory action of glucocorticoid upon the beta cell [14].…”
mentioning
confidence: 99%